Assessing Sustainability Literacy in Green School through Citizen Science Project on Biodiversity Learning - Hamidah, Nur; Hidayat, Topik; Sriyati, Siti; Hadibarata, Tony (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
The research aims to measure students' sustainability literacy after participating in a citizen science project. The subjects of this research were students at one of the state senior high schools (SMAN) in Bandung. The descriptive method with a quantitative approach was used in this research. The research was conducted over four weeks with a total of 12 hours of meetings in two classes with 72 students. Random sampling was used to establish the research sample. Data collection used assessment of students' sustainability literacy questions after they completed citizen science projects. Descriptive analysis was used to conclude the data. The finding shows that most students (93%) received passing grades above the minimum passing criteria (19.5% in sufficient, 55.5% good, and 18% excellent categories). It is shown that CSP-based learning is effective in strengthening the students' sustainability literacy.